Proposta de zoneamento ambiental para o município da Matola em Moçambique - Matule, Euclides Délio (2016)
The expansion of the urban area in the city of Matola in Mozambique has been significant in recent decades and it has happened in an unstructured way. This occupation contributes to the destruction of both the ecological and environmental structure of the city. One of the strategies to minimize these effects is to consider the legislation, concerning the urban land use and the preservation / conservation of vegetation, as well as the preparation of the Environmental Zoning. The main objective was, to propose an Environmental Zoning based on the analysis of urban sprawl and its impact on the environment, the distribution of vegetation over a period of 17 years (1997-2014) and the legislation to contribute with elements that inform and enable the development of urban and environmental planning in the municipality of Matola. Three satellite images from TM / Landsat 5 and OLI / Landsat 8 orbital sensor, SRTM data, population data and digital database of the city/country were utilized as input data. It was employed visual interpretation, images segmentations digital classification and geoprocessing technics. Results, indicated that urban area increased about 180.964m2, corresponding to 254.91% between 1997 and 2014. The area of vegetation cover reduced to 118.74m2 (52.62%) in 17 years. The Vegetation Cover Index (VCI) for total mapped area, reduced from, 61.25% in 1997, to 39.65% in 2007 and 29.02% in 2014. However, the detailed study of the VCI to different neighborhoods of Matola, showed a very uneven spatial distribution. The Environmental Zoning proposed, was made by integrating several information’s plans (thematic maps) and features five zones, namely: (i) Total Conservation Zone; (ii) Sustainable Use Conservation Zone; (iii) Expansion Urban Zone; (iv) Environmental Control Zone and (v) Recovery Zone. Has also proposed the creation of three protected areas located in the Total Conservation Zone: (i) Integral Natural Reserve, (ii) Natural Monument and (iii) Permanent Protection Green Area. This research will be important to municipal management and will serve as a basis for preparing the next general and partial urbanization plans and Matola Master Plan 2019/2020, achieving the objectives of the Environmental Strategy for Sustainable Development of Mozambique (2007 - 2017) and the objectives of Agenda 2030 of the UN.